(untitled) (Journal of humanities and social sciences exploratio, 2025)
This paper takes Dong Sheng and Li Shi, a classic play of Liyuan Opera, as the in-depth research object. Through close text reading and dramatic narratology analysis, it reveals that the play takes "awakening of passion and desire - conflict with Confucian ethics - liberation of human nature" as its implicit narrative thread. While maintaining the entertaining nature of a marketplace comedy, it realizes the critical reconstruction of feudal ethics. The study finds that the transformation of Dong Siwei in the play—from a Confucian scholar "afraid of ethics and laws" to a brave man "breaking through Confucian ethics"—is not only a typical manifestation of individual emotional strength breaking through rational discipline, but also an artistic projection of the awakening of humanistic consciousness among the citizen class in the mid-to-late Ming Dynasty. By deconstructing and reconstructing the "talented scholar and beautiful lady" model, the play completes a modern reflection on traditional moral ethics amid the dramatic tension of the confrontation between passion and reason, providing an important model for the contemporary transformation of classical dramas. Its innovative value lies in the organic integration of the entertaining function of marketplace comedies and the ideological depth of humanistic criticism, pioneering a new paradigm of "conveying reason through passion" in classical dramas.